History of One Document from the US National Archives: Memorandum of Conversation of the US Department of State - Petraitytė-Briedienė, Asta (Knygotyra, 2020)
The article briefly presents the US National Archives, where a number of documents important for the history of the Lithuanian diplomacy, as well as a document significant for the history of the Lithuanian diaspora and its political organizations, are preserved. One of them is Memorandum of Conversation dated 2 February 1949 and prepared by John D. Hickerson, an official of the US Department of State. It extensively describes his meeting and conversations with members of the Supreme Committee for the Liberation of Lithuania, the Prelate Mykolas Krupavičius and Vaclovas Sidzikauskas, who for the first time visited the US and were accompanied to the meeting by the then Lithuanian Envoy Extraordinary and Minister Plenipotentiary Povilas Žadeikis. Memorandum of Conversation is introduced into scientific circulation through methods of archival document monitoring and case analysis, as well as additional tools (such as periodicals and memoirs, archival documents) and based on the principles of document publication. The document published for the first time, as a primary source, supplements the data of Lithuanian historiography, gives a broader content to the known fact, reinforces the scientific research base on the history of Lithuanian diplomacy, the history of the Lithuanian diaspora’s political organizations and separately – the history of Lithuanian-the US bilateral diplomatic relations.
Keywords: NARA; the US Department of State; Lithuania; envoy; Lithuanian Freedom Case; the Supreme Committee for the Liberation of Lithuania